Civilian inattention and democratization: the Chilean military and political transition in the 1930s. Issue 1 (2nd January 2018) - Weeks, Gregory
ABSTRACT: The Chilean political transition that took place in 1932 is commonly viewed as positive for civil-military relations. This article argues that the very means used to restore stable civilian rule in Chile in the 1930s also contributed to the slow decay of civil-military relations, especially with the army. The conceptual lesson for the contemporary period is that civilian control entails much more than avoiding coups or rebellion in the short term. Civil-military institutions and civilian leadership matter for democracy. Although civilian strategies proved highly effective in the short term, the failure to strengthen civil-military institutions ultimately carried with it a high cost in the longer term. Compounded over years, civilian inattention can lead to estrangement, which in turn can gradually erode civilian supremacy and, by extension, democracy itself.